Tides & transgressions - Pasternak, Anne 1964- (Rizzoli Electa, 2022)
The first survey of the twenty-plus-year career of the highly influential multimedia artist Duke Riley, famous for expressing transgressive political and ecological themes through metaphors drawn from nautical folklore and nature. Duke Riley's work explores his lifelong fascination with urban waterways, their historical relationship to the culture of life at sea, and the uneasy intersections of human geography with the physical world. His work comments on a range of issues, from the cultural impact of overdevelopment and environmental destruction of waterfront communities to contradictions within political ideologies and the role of the artist in society. This comprehensive monograph collects work from his expansive career, encompassing drawings, sculptures, mosaics, performances, and more than one maritime adventure, including his Fly by Night public art project of pigeons illuminated by LED lights flying across the New York City skyline, documentation of his nefarious shell company Non-Essential Consultants, and the mayhem of the 2009 anarchic mock Roman naval battle, Those About to Die Salute You at the Queens Museum
"Published on the occasion of the exhibition, "Death to the Living, Long Live Trash", held at the Brooklyn Museum, NY, June 17, 2022-April 23, 2023."--Page 2
Some pages are on folded leaves, for example pages 73-80, 177-184
Keywords: Riley, Duke -- ca. 20./21. Jh.; Riley, Duke; Art / United States / 20th century; Art / United States / 21st century; Conceptual art / United States / Pictorial works; Performance art / United States; Birds in art / Pictorial works; Marine art / Pictorial works; Art; United States; 1900-2099; Exhibition catalogs; Ausstellungskatalog -- Brooklyn Museum -- 17.06.2022-23.04.2023 -- New York; Bildband